Dissecting the role of CSF2RB expression in human regulatory T cells - Côrte-Real, Beatriz F.; Arroyo Hornero, Rebeca; Dyczko, Aleksandra; Hamad, Ibrahim; Kleinewietfeld, Markus (Frontiers in Immunology, 2022)
Colony stimulating factor 2 receptor subunit beta (CSF2RB; CD131) is the common subunit of the type I cytokine receptors for granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-3 and IL-5. Interestingly, FOXP3+ regulatory T cells (Tregs), which play a pivotal role in prevention of autoimmunity have been demonstrated to highly overexpress CSF2RB and genome-wide association studies (GWAS) identified CSF2RB as being linked to autoimmune diseases like multiple sclerosis (MS). However, the exact biological role of CD131 in human Tregs has not been defined yet. Here we investigated CD131 importance on Treg phenotype and function in a broad range of in vitro studies. Although we could not recognize a specific function of (CSF2RB; CD131) in human Tregs, our data show that CD131 expression is vastly restricted to Tregs even under stimulatory conditions, indicating that CD131 could aid as a potential marker to identify Treg subpopulations from pools of activated CD4+ T cells. Importantly, our analysis further demonstrate the overexpression of CSF2RB in Tregs in patients with autoimmune disease like MS and systemic lupus erythematosus (SLE) in comparison to healthy controls, thereby indicating that CSF2RB expression in Tregs could serve as a potential novel biomarker for disease.